Never married women - Simon, Barbara Levy, 1949- (Women in the political economy., 1987)
""[Simon] deals seriously and perceptively with lives almost never granted such respect--those of the 'spinster, ' the 'old maid.' ... There is also a particular ironic energy.""--The Nation""Nothing is more ridiculous than someone who says, upon learning that I never got married, â€ ̃Oh, you would like my Aunt _____! She never got married either. You two would have a lot in common.' ""--an interview, August 1984. In this timely and provocative study, Barbara Levy Simon interviews fifty American women, born between 1884 and 1918 who were never married, and examines their emphatic ref.